An Analysis of Orientation Metaphor on BBC News about Covid-19 - A, Anisa (Al'Adzkiya Journal, 2022)
This study discusses the analysis of the orientation metaphor on BBC News about covid19. The objective of the study is to describe the conceptual metaphor, especially the orientation metaphor used on BBC News about Covid19. This research used the descriptive qualitative method. The data was taken from BBC News about covid19 in orientation metaphor. Based on the result of this research of the analysis of orientation metaphor on BBC News about Covid19, it was found that there was a total of 3 Headlines. The total occurrence from Orientation Metaphors in BBC News Headline about Covid19 Article ware they using spatial UP-DOWN like HAPPY IS UP and SAD IS DOWN occurrence